Notes on Love - Leth, Jorgen; Camre, Henning; Nissen, Claus; Ekblad, Stina; Nowicki, Jan (Danish Film Institute, 2007)
The film takes us to the Trobriand Islands, where the ethnographer Bronislaw Malinowski did his pioneering fieldwork in the 1920s, describing local sexual behaviour. No research project, Leth's film is more a collection of "notes", a sequence of soberly recording tableaux presenting love in its local forms of expression, while associatively cutting to similar forms of expression in Western culture and a fictitious writer's artistic desperation. [Cover]
Keywords: DVD-Video